A cross-scale ion rectifying membrane and a preparation method thereof
Patent Information
- Application Number
- CN202611297868.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本申请提供一种跨尺度离子整流隔膜及其制备方法,以解决现有锂离子电池隔膜作为电化学惰性多孔介质,无法抑制阴离子无功迁移且无法主动补偿浓差极化,导致电池能量效率难以突破性提升的技术问题
[0045]上述说明仅是本申请实施例技术方案的概述,为了能够更清楚了解本申请实施例的技术手段,而可依照说明书的内容予以实施,并且为了让本申请实施例的上述和其它目的、特征和优点能够更明显易懂,以下特举本申请的具体实施方式。
Smart Images

Figure CN122992282A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion battery separator technology, and in particular to a cross-scale ion rectifier separator and its preparation method. Background Technology
[0002] As a core component that isolates the positive and negative electrodes from electron contact and facilitates ion conduction, the ion transport characteristics of lithium-ion battery separators directly determine the battery's energy efficiency, rate performance, and cycle life. Current mainstream technology involves coating polyolefin-based membranes (such as polypropylene and polyethylene) with inorganic ceramic particles and polymer binders to form multilayer composite separators, balancing heat resistance, mechanical strength, and electrolyte wettability. To pursue superior electrochemical performance, multilayer coating schemes based on pore structure gradient control, enhanced interfacial adhesion, and optimized chemical stability have become the main development direction for separator technology.
[0003] Specifically, in terms of pore structure control, existing technologies construct interlayer porosity gradients using inorganic particles of different sizes to reduce ion transport resistance and improve electrolyte wettability. In terms of interface contact enhancement, existing technologies introduce an adhesive coating containing polyvinylidene fluoride onto the base film surface. Utilizing the adhesive force generated by the coating after swelling in the electrolyte and bonding with the electrode material, the membrane and electrode are integrated via hot pressing to reduce interfacial impedance. In terms of improving chemical stability, existing technologies employ an asymmetric coating design, configuring an oxidation-resistant polymer coating on the positive electrode side and a reduction-resistant polymer coating on the negative electrode side to specifically enhance the chemical stability and safety of both interfaces.
[0004] However, the aforementioned technical solutions all have fundamental limitations, causing bottlenecks in improving the energy efficiency of lithium-ion batteries. Existing separators are essentially electrochemically inert porous media, with ion transport entirely dependent on concentration gradients and passively driven by electric fields. Anions in the electrolyte undergo meaningless reverse migration under the influence of the electric field, causing severe transmembrane concentration polarization and directly reducing energy efficiency. Simultaneously, during high-rate charge and discharge, the lithium-ion concentration at the cathode / separator interface fluctuates drastically, generating instantaneous concentration overpotentials. Existing separators can only passively address this by optimizing porosity or interfacial wettability, unable to actively and instantly compensate for ion concentration. Furthermore, existing chemical stability designs are not effectively coupled with ion transport characteristics, failing to achieve the synergistic function of uniform ion flow and harmful substance capture. This results in the energy efficiency improvement of currently commercially available, optimal multilayer coated separators being only about 0.1%–0.2%, insufficient to meet the development needs of ultra-high energy-efficiency lithium-ion batteries.
[0005] Therefore, there is an urgent need for a cross-scale ion rectification separator and its preparation method to improve the energy efficiency of lithium-ion batteries. Summary of the Invention
[0006] This application provides a cross-scale ion rectification separator and its preparation method to solve the technical problem that existing lithium-ion battery separators, as electrochemically inert porous media, cannot suppress reactive migration of anions and cannot actively compensate for concentration polarization, resulting in difficulty in achieving breakthrough improvements in battery energy efficiency.
[0007] In a first aspect, this application provides a multi-scale ion rectification membrane, which, in the thickness direction from the positive electrode side to the negative electrode side, comprises: an anion repulsion layer, a supporting base film layer, and a cation enrichment and protection layer; the anion repulsion layer is a porous membrane with an average pore size of 20 nm to 80 nm, and the pore walls have fixed negatively charged groups; the supporting base film layer is a microporous membrane used to provide mechanical strength; the cation enrichment and protection layer is a porous membrane with an average pore size of 1 μm to 5 μm, and the pore walls contain electron-donating groups.
[0008] Through the above scheme, the fixed negatively charged groups on the pore walls of the anion repulsion layer ionize in the electrolyte to form a fixed negatively charged network. This fixed negatively charged network, through electrostatic repulsion, repels lithium salt anions (such as PF6) in the electrolyte. -The transmembrane transport resistance is increased by more than two orders of magnitude, while the resistance to lithium-ion conduction is almost negligible. This allows the separator to selectively and preferentially transport lithium ions, significantly increasing the lithium-ion transport number. This significant increase in the lithium-ion transport number means that during charging and discharging, over 50% of the transmembrane current is carried by lithium ions that effectively perform work, while reactive anion migration is greatly suppressed. Reactive anion migration is the main cause of transmembrane concentration polarization; by reducing this polarization loss at its source, the battery's energy efficiency is significantly improved. The electron-donating groups (such as amino-NH2) on the pore walls of the cation enrichment and protective layer contain lone pairs of electrons, which can weakly coordinate with lithium ions. As lithium ions pass through the anion repulsion layer and the supporting substrate layer and are about to reach the negative electrode interface, the densely distributed electron-donating groups on the pore walls of the cation enrichment and protective layer continuously perform alternating "coordination-decoordination" interactions with the lithium ions. This process is equivalent to applying transient, periodic regulation to the transmembrane movement of lithium ions, homogenizing the lithium ion flux that would otherwise tend to accumulate in local hot spots (such as at the membrane pores). Once the homogenized lithium ion flow reaches the negative electrode surface, lithium metal can be uniformly deposited, significantly suppressing the non-uniform nucleation and growth of lithium dendrites. The reduction in lithium dendrites directly lowers the risk of internal short circuits in the battery, improving its safety during long-term cycling. The anion repulsion layer has an average pore size of 20 nm to 80 nm, belonging to the nanoscale pore size; the cation enrichment and protection layer has an average pore size of 1 μm to 5 μm, belonging to the microscale pore size. These two layers form a continuous transition through the microporous structure supporting the base film, creating a cross-scale pore size gradient from nanoscale to microscale along the membrane thickness direction. The superiority of this structural design lies in the following: the nanoscale pores of the anion repulsion layer provide a high specific surface area, ensuring a sufficiently high volume density of fixed negatively charged groups, thus making the electrostatic repulsion effect fully effective; simultaneously, the nanoscale pore size allows solvated lithium ions to pass through smoothly, while creating a dual physical and electrostatic barrier to the migration of anions. The micron-sized macropores (finger-like through-pore structure) of the cation enrichment and protection layer provide a low-resistance release channel for lithium ions after selective sieving, enabling lithium ions to quickly escape from the membrane and enter the negative electrode interface, avoiding the contradiction of "sacrificing sieving precision and conduction flux" caused by a single pore size. The synergistic effect of the above three layers allows the membrane to precisely sieve ion types on the positive electrode side and efficiently release effective ions on the negative electrode side, achieving a balance between selectivity and permeability.
[0009] In one possible design, the membrane further includes an ion transport enhancement layer disposed between the anion repulsion layer and the supporting substrate layer; the ion transport enhancement layer comprises a piezoelectric material.
[0010] Through the above scheme, the piezoelectric material in the ion transport enhancement layer exhibits a positive piezoelectric effect. During battery charge-discharge cycles, the electrode active material undergoes reversible volume expansion and contraction (deformation typically <2%). This mechanical deformation is transmitted to the ion transport enhancement layer through the anion repulsion layer, compressing the piezoelectric material within it, causing lattice distortion and generating a momentary piezoelectric potential difference. The direction of this potential difference is aligned with the direction of lithium ion migration from the positive to the negative electrode, serving as an additional driving force to actively accelerate the transmembrane transport of lithium ions. The ion transport enhancement layer is positioned close to the anion repulsion layer to receive electrode deformation nearby and generate a piezoelectric response, allowing the driving force to act directly on the lithium ions that have just undergone selective sieving through the anion repulsion layer, achieving the effect of "immediate acceleration after sieving".
[0011] In one possible design, the ion transport enhancement layer comprises a composite material of a piezoelectric material and an ion-conducting polymer; wherein the piezoelectric material is at least one piezoelectric ceramic nanoparticle selected from tetragonal barium titanate, lead zirconate titanate, and potassium sodium niobate, or a β-crystal piezoelectric polymer of polyvinylidene fluoride-trifluoroethylene copolymer; and the ion-conducting polymer comprises polyethylene oxide and lithium bis(trifluoromethanesulfonylimide).
[0012] Through the above methods, tetragonal barium titanate (BaTiO3) exhibits excellent piezoelectric coefficients, while lead zirconate titanate (PZT) and potassium sodium niobate (KNN) are also recognized as high-performance piezoelectric ceramic materials. These piezoelectric materials maintain stable piezoelectric activity at the nanoparticle scale, generating sufficient transient potential difference even under minute deformations of the battery electrodes. This potential difference is sufficient to significantly accelerate the transmembrane migration of lithium ions. Polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE), in its β-crystal form, is a piezoelectric polymer. Although its piezoelectric coefficient is slightly lower than that of piezoelectric ceramics, it possesses advantages such as good flexibility, low density, and solution-forming capabilities. Furthermore, as a polymer material itself, it exhibits excellent compatibility with ion-conducting polymers, allowing for the formation of continuous and stable integrated composite films without the need for additional binders.
[0013] In one possible design, the ion transport enhancement layer has a thickness of 1 μm to 3 μm and an average pore size of 50 nm to 200 nm.
[0014] Through the above scheme, the thickness of the ion transport enhancement layer is limited to 1 μm to 3 μm. Within this thickness range, the total amount of piezoelectric material contained in the ion transport enhancement layer is sufficient to generate a considerable piezoelectric response signal. The thicker the layer, the larger the total amount of piezoelectric material, and the higher the total potential generated. At the same time, the thickness is not too large, avoiding the loss of battery energy density and the significant increase in the total ion transmembrane impedance caused by increasing the total thickness of the separator. When the thickness is less than 1 μm, the piezoelectric material content is insufficient, the piezoelectric response is weak, and it is difficult to generate an effective ion driving effect. When the thickness is greater than 3 μm, the total impedance of the separator increases significantly, and the increased amount of piezoelectric material drives up the cost. At the same time, the negative impact of adding the B layer on the battery energy density begins to appear. The thickness window of 1 μm to 3 μm is the optimal range obtained after optimizing the balance between piezoelectric driving effect, ion conduction resistance, and battery energy density. The average pore size of the ion transport enhancement layer is limited to 50 nm to 200 nm. This pore size range is sufficiently large to accommodate piezoelectric ceramic nanoparticles with an average particle size of approximately 100 nm to 200 nm. These nanoparticles can be embedded in the pores or distributed on the pore wall surface, forming a continuous piezoelectric response network while ensuring the smooth passage of lithium ions. The effective size of lithium ions and solvated lithium ions is much smaller than this pore size. Furthermore, this pore size range ensures that the ion transport enhancement layer has a sufficient specific surface area, which is beneficial for close contact and interfacial charge transfer between the piezoelectric material and the ion-conducting polymer. When the pore size is below 50 nm, it is difficult to effectively accommodate piezoelectric ceramic nanoparticles, and the ion conduction resistance increases significantly. When the pore size is above 200 nm, the contact area between the piezoelectric material and the ion-conducting polymer decreases, and the conversion efficiency of piezoelectric potential to ion driving force decreases.
[0015] In one possible design, the thickness of the anion repulsion layer is 2 μm to 5 μm; the supporting base membrane layer is a polypropylene microporous membrane or a polyethylene microporous membrane with a thickness of 5 μm to 25 μm; and the thickness of the cation enrichment and protection layer is 5 μm to 10 μm.
[0016] Through the above scheme, the thickness of the anion repulsion layer is limited to 2 μm to 5 μm. Within this thickness range, the anion repulsion layer has sufficient graft layer thickness to support a high density of fixed negatively charged groups, forming an effective electrostatic repulsion field; at the same time, the thickness is not too large, avoiding a significant increase in lithium-ion transmembrane impedance due to excessive layer thickness. When the thickness is less than 2 μm, the total amount of fixed negatively charged groups is insufficient, the electrostatic repulsion effect's ability to block anions decreases, and the increase in lithium-ion transference number is limited; when the thickness is greater than 5 μm, the path of lithium ions through the layer is lengthened, the impedance increases, and partially offsets the energy efficiency gain brought by selective transport.
[0017] The supporting base membrane layer is made of polypropylene (PP) or polyethylene (PE) microporous membrane. These materials are the most mature and widely used commercial base membrane materials in the field of lithium-ion battery separators, and have the comprehensive advantages of low cost, stable supply, good chemical stability, and moderate mechanical strength. The thickness of the supporting base membrane layer is 5 μm to 25 μm, providing an adjustable mechanical strength window.
[0018] The thickness of the cation enrichment and protective layer was limited to 5 μm–10 μm. Within this thickness range, the cation enrichment and protective layer possesses sufficient polymer matrix volume to accommodate ample electron-donating groups (-NH2), ensuring sufficient chemical capture capability of HF in the electrolyte (thickness is positively correlated with capture capacity) and sufficient homogenization effect of lithium-ion flow (thickness is positively correlated with the number of coordination-decoupling interactions). Simultaneously, the finger-like macroporous structure of the cation enrichment and protective layer ensures smooth release of lithium ions from this layer to the negative electrode interface. When the thickness is less than 5 μm, the total amount of functional groups is insufficient, limiting the effectiveness of HF capture and lithium-ion homogenization; when the thickness is greater than 10 μm, the total thickness of the separator increases, and the negative impact on battery energy density begins to appear.
[0019] In one possible design, the anion repellent layer is composed of a matrix material grafted with fixed negatively charged groups; wherein the fixed negatively charged groups are sulfonic acid groups or carboxyl groups; the matrix material includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polypropylene, polyethylene, sulfonated polyether ether ketone, and perfluorosulfonic acid resin.
[0020] Through the above scheme, the negatively charged group is fixed as a sulfonic acid group (-SO3). - ) or carboxyl group (-COO) - Sulfonic acid groups are strongly acidic and can ionize significantly in both aqueous and non-aqueous electrolytes, forming a high-density network of fixed negative charges. Their charge density ranks among the highest of commonly used fixed-charge groups, making them a preferred option for constructing efficient electrostatic repulsion fields. Carboxyl groups can also ionize in electrolytes to generate fixed negative charges. Furthermore, carboxyl groups are widely available and can be introduced using various methods, making them suitable for cost-sensitive applications or those requiring simplified processes.
[0021] Polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) has good film-forming properties and high chemical stability, making it easy to introduce sulfonic acid groups or carboxyl groups through irradiation grafting or chemical grafting.
[0022] Polypropylene (PP) and polyethylene (PE) can be directly surface-grafted onto existing commercial PP or PE microporous membranes without additional film-forming steps, offering the best compatibility with existing diaphragm production lines and the lowest modification costs.
[0023] Sulfonated polyether ether ketone (SPEEK) and perfluorosulfonic acid resin are ionomer materials with sulfonic acid groups, requiring no additional grafting or chemical modification steps. The membrane itself has a high density of fixed negative charge groups, making the process relatively simple.
[0024] In one possible design, the cation enrichment and protective layer is made of polyethyleneimine and an aminosilane coupling agent via a phase inversion method; the electron-donating group is amino.
[0025] Through the above scheme, polyethyleneimine (PEI) is a branched or linear polymer rich in amino groups (-NH2). Each side chain of its molecular chain contains primary, secondary, and tertiary amine groups, resulting in a high amino density. This high amino density provides sufficient functional sites for cation enrichment and the protective layer.
[0026] The aminosilane coupling agent (KH-550, γ-aminopropyltriethoxysilane) contains both amino and silane terminals. Its silane terminal (triethoxysilane group) can chemically react with trace amounts of hydroxyl groups on the surface of the polypropylene or polyethylene support film to form Si-OC or Si-O-Si chemical bonds, firmly anchoring the cation enrichment and protective layer to the surface of the support film. Compared to coatings that rely solely on physical adhesion, the interfacial bonding strength of the chemical bond is significantly improved, effectively preventing the cation enrichment and protective layer from peeling or detaching due to electrolyte immersion and electrode volume deformation during long-term battery cycling. Its amino terminal synergistically interacts with the amino group of polyethyleneimine, jointly participating in lithium-ion coordination and HF chemical capture. KH-550 simultaneously plays the dual role of "interface enhancer" and "functional synergist" in the cation enrichment and protective layer.
[0027] The advantages of using the phase transformation method to prepare cation enrichment and protective layer are: (1) The pore structure formed is a finger-shaped macropore (finger-shaped through pore). This pore type has the lowest tortuosity and the highest permeability among many porous structures, and has the least resistance to lithium ion conduction; (2) During the phase transformation process, the polymer-rich phase solidifies into pore walls, and the polymer-poor phase evolves into pores. Hydrophilic amino groups tend to be enriched on the surface of the pore walls during the phase transformation process (because amino groups are hydrophilic and more stable in water coagulation bath), thereby achieving effective exposure of functional groups on the surface of the pore walls.
[0028] In one possible design, the mass ratio of polyethyleneimine to aminosilane coupling agent is 8:1 to 10:1.
[0029] Through the above scheme, when the mass ratio of polyethyleneimine to aminosilane coupling agent is less than 8:1, although the interfacial bonding strength is further improved, the proportion of polyethyleneimine is relatively reduced, and the density of amino functional sites is insufficient to achieve adequate lithium-ion flow homogenization and HF capture. When the mass ratio of polyethyleneimine to aminosilane coupling agent is greater than 10:1, the KH-550 content is insufficient, the number of chemical bonding sites between the cation enrichment and protective layer and the polypropylene or polyethylene supporting film layer is insufficient, the interfacial bonding strength decreases, and the cation enrichment and protective layer may peel off from the surface of the supporting film layer during long-term cycling, leading to functional failure.
[0030] In a second aspect, this application provides a method for preparing a cross-scale ion rectifying membrane as described in the first aspect, comprising the steps of: forming an anion repulsion layer, wherein the anion repulsion layer has an average pore size of 20 nm to 80 nm and the pore walls have fixed negatively charged groups; forming a supporting base film layer, wherein the supporting base film layer is a microporous membrane; forming a cation enrichment and protection layer, wherein the cation enrichment and protection layer is a porous membrane with an average pore size of 1 μm to 5 μm and the pore walls contain electron-donating groups; aligning the anion repulsion layer, the supporting base film layer, and the cation enrichment and protection layer sequentially from the positive electrode side to the negative electrode side in the thickness direction, and hot-pressing composite to form a cross-scale ion rectifying membrane.
[0031] The above method involves forming the anion repulsion layer, the supporting substrate layer, and the cation enrichment and protective layer separately before composite formation. The formation of the anion repulsion layer involves a chemical grafting reaction (such as gamma-ray irradiation grafting), with relatively harsh reaction conditions (irradiation dose, monomer concentration, and reaction atmosphere). The formation of the cation enrichment and protective layer involves a phase transformation process, and its coagulation bath conditions are completely incompatible with the grafting reaction conditions. Independent preparation of each functional layer avoids interference between the aforementioned process conditions, allowing each layer to form under its optimal process conditions, thus ensuring the structural integrity and functional stability of each layer.
[0032] In one possible design, forming the anion repellent layer includes the following steps: immersing a polymer porous membrane in a mixed aqueous solution containing styrene sulfonate monomer and acrylic acid; grafting the membrane under an inert atmosphere by co-irradiation with cobalt-60 gamma rays at an absorbed dose of 10 kGy to 15 kGy; washing and drying the grafted membrane to obtain an anion repellent layer grafted with sulfonic acid groups. Forming the cation enrichment and protective layer includes the following steps: dissolving polyethyleneimine and an aminosilane coupling agent in N-methylpyrrolidone at a mass ratio of (8 to 10):1 to form a casting solution; coating the casting solution onto the side of the supporting substrate membrane near the negative electrode; and then immersing the membrane in water for phase inversion to obtain the cation enrichment and protective layer.
[0033] The above scheme utilizes co-irradiation grafting with cobalt-60 gamma rays to simultaneously initiate graft copolymerization reactions on the surface and internal pore walls of the polymer porous membrane, leveraging the high penetrability of gamma rays. This achieves uniform chemical bonding of sulfonic acid groups in the three-dimensional structure of the membrane, forming a stable and non-soluble fixed negative charge network, ensuring a long-lasting and stable electrostatic repulsion effect against anions. Simultaneously, by controlling the absorbed dose within the range of 10 kGy to 15 kGy, the grafting rate can be precisely controlled to match different pore size requirements (10 kGy corresponds to a simplified scheme for larger pore sizes, while 15 kGy corresponds to the optimal scheme for smaller pore sizes). This ensures a high grafting rate to form a dense negative charge field while avoiding excessive irradiation that could lead to matrix degradation, thus achieving a balance between anion selective sieving efficiency and membrane mechanical properties.
[0034] The casting solution of polyethyleneimine and aminosilane coupling agent is subjected to liquid-liquid phase separation in a coagulation bath via an aqueous phase inversion method, forming an in-situ cation enrichment and protection layer with a finger-like, interconnected macroporous structure. This pore type has low tortuosity and excellent permeability, ensuring minimal resistance when lithium ions pass through the layer and preventing it from becoming a bottleneck for ion conduction. Simultaneously, the hydrophilic amino groups tend to segregate and enrich towards the pore wall surface during the phase inversion process, achieving effective exposure of functional groups at the solid-liquid interface. This ensures the coordination homogenization effect of amino groups on lithium ions and the chemical capture efficiency of corrosive HF. Furthermore, by controlling the mass ratio of polyethyleneimine to aminosilane coupling agent within the range of 8:1 to 10:1, sufficient amino density is ensured to fully exert its function, while maintaining sufficient coupling agent content to ensure a strong chemical bond between the layer and the polyolefin support film layer, preventing delamination during long-term cycling.
[0035] In one possible design, an ion transport enhancement layer is formed between the anion repulsion layer and the supporting substrate layer, the ion transport enhancement layer comprising a piezoelectric material.
[0036] The above scheme utilizes an ion transport enhancement layer containing piezoelectric materials to generate a piezoelectric effect by utilizing the mechanical stress caused by electrode volume deformation during battery charging and discharging. This generates a transient potential difference in situ that aligns with the lithium-ion migration direction, serving as an additional driving force to actively accelerate lithium-ion transmembrane transport. This effectively compensates for the interfacial concentration polarization caused by lithium-ion supply lag during high-rate charging and discharging. Simultaneously, this ion transport enhancement layer is positioned adjacent to the anion repulsion layer, enabling it to receive electrode deformation nearby and directly apply the driving force to the lithium-ions that have just undergone selective sieving. This achieves functional coupling of ion sieving and active transport, transforming the separator from a passive conductive medium into an intelligent ion device with active ion management capabilities.
[0037] In one possible design, forming the ion transport enhancement layer includes the steps of: mixing and dispersing a piezoelectric material with an ion-conducting polymer in an organic solvent to form a slurry, coating the slurry onto the surface of an anion repulsion layer, and vacuum drying to obtain the ion transport enhancement layer.
[0038] The above scheme involves mixing piezoelectric materials with ion-conducting polymers to form a slurry, which is then coated onto the surface of the anion repulsion layer. This allows the ion transport enhancement layer to solidify in situ, resulting in a tight molecular-level contact between the layers. This ensures that electrode deformation can be efficiently transferred to the piezoelectric material through the anion repulsion layer, avoiding deformation transfer loss and piezoelectric response attenuation due to poor interlayer interface. Simultaneously, the slurry coating method allows for precise control of the wet film thickness. Combined with vacuum drying to remove organic solvents, this yields a functional layer with uniform thickness, uniformly dispersed piezoelectric ceramic particles, and a continuous ion conduction path. This ensures sufficient piezoelectric response strength while avoiding increased membrane impedance due to excessive thickness.
[0039] In one possible design, the piezoelectric material is tetragonal barium titanate nanoparticles, and the ion-conducting polymer includes polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide; the mass ratio of tetragonal barium titanate nanoparticles, polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide is (65~75):(20~30):(3~8). By employing tetragonal barium titanate nanoparticles as piezoelectric materials, sufficient transient potential difference can be generated under small deformations using their high piezoelectric coefficient. A continuous conduction pathway for lithium ions is provided by the polyethylene oxide matrix, and lithium bis(trifluoromethanesulfonylimide) serves as a supplementary lithium salt ion source. This allows the ion transport enhancement layer to possess both efficient piezoelectric drive and excellent ion conduction. Furthermore, by controlling the mass ratio of the three components within the range of (65~75):(20~30):(3~8), sufficient piezoelectric ceramic filling is ensured to generate a strong piezoelectric response, while maintaining adequate coating of the ceramic particles by the polymer matrix and the integrity of the continuous ion conduction channel. The introduction of an appropriate amount of lithium salt further enhances the intrinsic ionic conductivity of the layer, enabling the driving force generated by the piezoelectric effect to be efficiently converted into the transmembrane migration kinetic energy of lithium ions.
[0040] In one possible design, the temperature for hot-pressing is 50~60℃ and the pressure is 0.3~0.5 MPa.
[0041] The above scheme controls the hot-pressing temperature at 50~60℃, allowing the polyethylene oxide in the ion transport reinforcement layer to soften sufficiently within this temperature range, generating a viscous flow state. This allows the hot melt adhesive to firmly bond adjacent layers. Simultaneously, this temperature is lower than the thermal shrinkage initiation temperature of the polyolefin support base film, avoiding problems such as base film dimensional deformation and porosity reduction during hot pressing. Combined with a pressure range of 0.3~0.5 MPa, this is sufficient to expel interlayer air and promote interfacial molecular chain interpenetration for tight bonding, while preventing excessive pressure from collapsing the porous structure of each functional layer. Thus, while ensuring interlayer bonding strength, the pore size parameters and ion conductivity of each layer are maintained.
[0042] In one possible design, the thickness of the anion repulsion layer is 2 μm to 5 μm; the thickness of the supporting base film layer is 5 μm to 25 μm; and the thickness of the cation enrichment and protection layer is 5 μm to 10 μm.
[0043] The above scheme limits the thickness of the anion repulsion layer to 2μm~5μm, ensuring sufficient graft layer thickness to support the high-density fixed negatively charged groups and form an effective electrostatic repulsion field, while avoiding a significant increase in lithium-ion transmembrane impedance due to excessive thickness. The thickness of the supporting base film layer is limited to 5μm~25μm, providing sufficient support for the separator. The thickness of the cation enrichment and protective layer is limited to 5μm~10μm, ensuring sufficient polymer matrix volume to accommodate high-density amino functional groups, guaranteeing adequate homogenization of the lithium-ion flow and sufficient chemical capture capacity for corrosive HF in the electrolyte. Simultaneously, its internal finger-like interconnected macroporous structure ensures low impedance characteristics during ion release. The synergistic optimization of the three layer thicknesses achieves the best balance between full functional realization and minimized impedance in the separator.
[0044] Thirdly, this application provides a lithium-ion battery comprising a cross-scale ion rectifier separator as described in any of the first aspects, or comprising a cross-scale ion rectifier separator prepared by any of the preparation methods in the second aspect.
[0045] The above description is merely an overview of the technical solutions of the embodiments of this application. In order to better understand the technical means of the embodiments of this application and to implement them in accordance with the contents of the specification, and to make the above and other objects, features and advantages of the embodiments of this application more obvious and understandable, specific implementation methods of this application are described below. Attached Figure Description
[0046] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0047] Figure 1 This is a schematic diagram of the cross-sectional structure of a multi-scale ion rectifier diaphragm provided in one embodiment of this application.
[0048] Figure 2 This is a schematic diagram of the cross-sectional structure of the multi-scale ion rectifier diaphragm provided in another embodiment of this application.
[0049] Explanation of reference numerals in the attached figures: 10. Anion repulsion layer; 20. Ion transport enhancement layer; 30. Supporting base film layer; 40. Cation enrichment and protection layer. Detailed Implementation
[0050] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein in the specification of the application is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims and drawings of this application are intended to cover non-exclusive inclusion.
[0052] The term "embodiment" as used herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of the phrase "embodiment" in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0053] In this article, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can mean: A exists, A and B exist simultaneously, or B exists. Additionally, the character " / " in this article generally indicates that the preceding and following related objects have an "or" relationship.
[0054] In the description of this application, unless otherwise stated, "multiple" means two or more (including two), and similarly, "multiple groups" means two or more (including two groups).
[0055] In the description of this application, the term "positive electrode side" refers to the side of the separator facing the positive electrode plate when used in a lithium-ion battery, and the term "negative electrode side" refers to the side of the separator facing the negative electrode plate when used in a lithium-ion battery. "Thickness direction" refers to the direction perpendicular to the separator from the positive electrode side surface to the negative electrode side surface. "Average pore size" refers to the arithmetic mean obtained by statistically analyzing the equivalent diameters of no fewer than 100 pores after observing the separator cross-section using a field emission scanning electron microscope and using image analysis software.
[0056] As can be seen from the background technology, the current improvement in energy efficiency of the best commercially available multilayer coated separators is insufficient to meet the development needs of ultra-high energy efficiency lithium-ion batteries.
[0057] In related technologies, various membrane modification strategies are employed. For example, physical coating methods apply inorganic ceramic particles (such as alumina and boehmite), organic polymers, or nanofibers to the surface of the base membrane to improve heat resistance, mechanical strength, and electrolyte wettability. Chemical grafting introduces functional groups onto the membrane surface through covalent bonding, improving interfacial compatibility and ion transport capacity. At the structural design level, asymmetric composite membranes have become an important development direction—by coating different functional coatings on both sides of the base membrane, differentiated designs are made for the electrochemical environments on the positive and negative electrode sides to simultaneously meet multiple requirements such as interfacial adhesion, chemical stability, and ion transport.
[0058] Although the aforementioned modification strategies have achieved significant progress in terms of thermal stability, wettability, and interfacial adhesion, existing technologies have a fundamental limitation: regardless of the coating or grafting modification employed, the separator itself remains an electrochemically inert porous medium. During battery charging and discharging, lithium salt anions (such as PF6)... - Lithium ions migrate in the reverse direction under the drive of an electric field. This process does no work but causes severe transmembrane concentration polarization, directly reducing the battery's energy efficiency. Lithium-ion transport number (t_(Li + The ratio of lithium-ion carrying current to the total ion current is a quantitative indicator for measuring this loss; the current commercially optimal separator has a t_(Li) ratio of lithium-ion carrying current to the total ion current. +The ion current value is typically only 0.3~0.35, meaning that over 65% of the ion current is contributed by reactive migration of anions. Although some studies have explored functionalization modifications to enhance t_(Li) + The efficiency of the modified layer has been increased to above 0.6, but most of them focus on a single function (such as anion adsorption or ion flow homogenization). There are no reports of integrating anion electrostatic repulsion and active ion driving mechanisms in the same thickness direction of the membrane.
[0059] Furthermore, under high-rate charge-discharge conditions, the instantaneous concentration overpotential caused by drastic fluctuations in lithium-ion concentration at the cathode / separator interface is another key factor limiting the energy efficiency of high-power output. Existing separators can only passively address ion transport demands by optimizing porosity or improving wettability, but cannot actively and promptly provide a compensating driving force for the lithium-ion deficit at the interface.
[0060] In view of this, embodiments of this application provide a cross-scale ion rectifier separator that can actively manage ion transport—selectively sieving cations and anions to suppress reactive migration, and dynamically accelerating lithium-ion cross-membrane replenishment according to operating conditions—to break through the current energy efficiency bottleneck of lithium-ion batteries and achieve high power and high energy efficiency.
[0061] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings.
[0062] Example 1 Figure 1 This is a schematic diagram of the cross-sectional structure of the multi-scale ion rectifying membrane provided in this embodiment. Figure 1 As shown, this application provides a cross-scale ion rectification membrane with a four-layer structure. The membrane includes, in the thickness direction from the positive electrode side to the negative electrode side, an anion repulsion layer 10, an ion transport enhancement layer 20, a supporting base film layer 30, and a cation enrichment and protection layer 40.
[0063] An anion repellent layer 10 is disposed on the positive electrode side and is in direct contact with the positive electrode plate of the battery during use. The anion repellent layer 10 is composed of a porous membrane of polyvinylidene fluoride-hexafluoropropylene copolymer grafted with sulfonic acid groups, with an average pore size of 35 nm. The pore wall surface of the anion repellent layer 10 is grafted with sulfonic acid groups, which ionize in the electrolyte to form a fixed negative charge network. This fixed negative charge network resists lithium salt anions (such as PF6) in the electrolyte. - This generates Coulomb repulsion, increasing the resistance to transmembrane transport of anions by more than two orders of magnitude, while producing almost no additional resistance to lithium-ion conduction. The thickness of the anion repulsion layer 10 is 5 μm.
[0064] An ion transport enhancement layer 20 is disposed on the side of the anion repulsion layer 10 near the negative electrode, located between the anion repulsion layer 10 and the supporting substrate layer 30. The ion transport enhancement layer 20 comprises a composite material of a piezoelectric material and an ion-conducting polymer. The piezoelectric material is tetragonal barium titanate nanoparticles with an average particle size of 150 nm; the ion-conducting polymer comprises polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide, with polyethylene oxide serving as the lithium-ion conducting medium and lithium bis(trifluoromethanesulfonyl)imide serving as a lithium salt supplementary lithium-ion source. The ion transport enhancement layer 20 has a thickness of 2 μm and an average pore size of 100 nm.
[0065] During battery charge-discharge cycles, the electrode active material undergoes reversible volume expansion and contraction, resulting in minute mechanical deformation. This deformation is transmitted through the anion repulsion layer 10 to the ion transport enhancement layer 20, compressing the tetragonal barium titanate nanoparticles and causing lattice distortion, generating a transient piezoelectric potential difference. The direction of this potential difference is consistent with the direction of lithium ion migration from the positive electrode to the negative electrode, serving as an additional driving force to actively accelerate the transmembrane transport of lithium ions.
[0066] The supporting base film layer 30 is disposed on the side of the ion transport enhancement layer 20 near the negative electrode, serving as the mechanical framework of the entire separator. The supporting base film layer 30 is a polypropylene microporous membrane with a thickness of 16 μm, an average pore size of 120 nm, and a porosity of approximately 45%. The supporting base film layer 30 is a commercially available separator substrate, providing an adhesion substrate and mechanical support for the anion repulsion layer 10, the ion transport enhancement layer 20, and the cation enrichment and protection layer 40, ensuring the dimensional stability and puncture resistance of the separator during battery assembly and cycling.
[0067] The cation enrichment and protection layer 40 is disposed on the side of the supporting base film layer 30 near the negative electrode, and is in direct contact with the negative electrode sheet of the battery during use. The cation enrichment and protection layer 40 is made of polyethyleneimine and an aminosilane coupling agent by phase inversion, with a mass ratio of polyethyleneimine to aminosilane coupling agent of 9:1. The cation enrichment and protection layer 40 has a finger-like macroporous structure, with amino groups on the pore walls, an average pore size of 2 μm to 3 μm, and a thickness of 7 μm.
[0068] The amino groups on the 40-pore wall of the cation enrichment and protection layer have a dual function: First, the nitrogen atoms on the amino groups have lone pairs of electrons, which can weakly coordinate with lithium ions. Through the alternating coordination-decoupling process, the lithium ion flow at the interface is homogenized, avoiding uneven lithium deposition caused by excessively high local ion concentrations, thereby inhibiting the growth of lithium dendrites. Second, as Lewis bases, the amino groups can undergo acid-base coordination reactions with hydrogen fluoride, a corrosive substance in the electrolyte, chemically capturing and fixing hydrogen fluoride on the pore wall, preventing hydrogen fluoride from diffusing to the negative electrode surface and eroding the SEI film.
[0069] The total thickness of the four-layer structure, consisting of anion repulsion layer 10, ion transport enhancement layer 20, supporting base film layer 30, and cation enrichment and protection layer 40, is 20 μm.
[0070] The preparation method of the cross-scale ion rectifier membrane in this embodiment is as follows.
[0071] Preparation of anion repulsion layer 10: A polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) porous membrane with a thickness of 5 μm and an average pore size of approximately 30 nm was used as the substrate material. The PVDF-HFP membrane was cut into 20 cm × 20 cm specimens, and ultrasonically cleaned in acetone and anhydrous ethanol for 15 minutes each, followed by vacuum drying at 60 °C for 2 hours for later use.
[0072] Preparation of grafting reaction solution: Dissolve sodium styrene sulfonate (SSS, purity ≥99%) and acrylic acid (AA, purity ≥99.5%) in deionized water, with the mass fraction of sodium styrene sulfonate being 15% and the mass fraction of acrylic acid being 5%. Purge the grafting reaction solution with high-purity nitrogen gas (purity ≥99.999%) for 30 minutes to remove dissolved oxygen.
[0073] The pretreated PVDF-HFP membrane was completely immersed in the grafting reaction solution, with 1 g of membrane corresponding to 100 mL of solution. The membrane was sealed in a polyethylene bag, and nitrogen gas was continuously introduced to maintain an inert atmosphere. The sealed bag was then placed in a cobalt-60 gamma-ray irradiation device for co-irradiation grafting. The absorbed dose was set to 15 kGy, the dose rate was 2 kGy / h, and the irradiation temperature was room temperature (25 ± 2 °C).
[0074] After irradiation, the grafted membrane was removed and washed six times (30 minutes each time) with deionized water at 60°C with shaking to thoroughly remove unreacted monomers and homopolymers adhering to the membrane surface. The grafted membrane was then vacuum-dried at 60°C for 12 hours to constant weight, yielding anion repulsion layer 10. The grafting rate was determined to be approximately 35%–40% by gravimetric analysis. Field emission scanning electron microscopy (FESEM) observation of the membrane cross-section showed an average pore size of approximately 35 nm. Elemental analysis of the membrane surface using X-ray photoelectron spectroscopy (XPS) detected a distinct S 2p characteristic peak (binding energy approximately 168.5 eV), confirming the successful grafting of sulfonic acid groups onto the membrane surface and pore walls.
[0075] Preparation of ion transport enhancement layer 20: Tetragonal barium titanate nanoparticles with high piezoelectric coefficient (average particle size of about 150 nm, piezoelectric constant d33≈190pC / N) were selected and vacuum dried at 120℃ for 4 hours before use to remove surface adsorbed moisture.
[0076] Weigh out 7.0 g of tetragonal barium titanate nanoparticles, 2.5 g of polyethylene oxide (PEO), and 0.5 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), with a mass ratio of 70:25:5. Add the above solid materials to 100 mL of anhydrous acetonitrile (moisture content <10 ppm) and place in a planetary ball mill at 300 rpm for 6 hours. A zirconia ball mill jar and zirconia balls with a diameter of 5 mm (ball-to-material mass ratio 5:1) can be used to obtain a uniformly dispersed and stable slurry.
[0077] An automatic coating machine was used to coat the above slurry onto the surface of the anion repulsion layer 10 with a wet film thickness of 50 μm on one side. The coating speed was 2 m / min. Immediately after coating, the layer was transferred to a vacuum drying oven and dried at 60℃ and a vacuum degree ≤ -0.095 MPa for 12 hours to obtain the ion transport enhancement layer 20. Field emission scanning electron microscopy (FESEM) cross-section observation showed that the ion transport enhancement layer 20 had a uniform thickness, averaging approximately 2.0 μm. The barium titanate particles were well dispersed in the vinyl oxide matrix without obvious agglomeration. The layer exhibited a sponge-like interconnected pore structure with an average pore size of approximately 100 nm.
[0078] Cation enrichment and preparation of protective layer 40 on supporting film layer 30: A commercially available polypropylene microporous membrane with a thickness of 16 μm, a porosity of approximately 45%, and an average pore size of approximately 120 nm was selected as the supporting substrate layer 30. Before use, the polypropylene membrane was cut into 20cm × 20cm test pieces, ultrasonically cleaned in anhydrous ethanol for 10 minutes, and then air-dried at room temperature.
[0079] Preparation of casting solution: Polyethyleneimine (PEI) and aminosilane coupling agent (KH-550) are mixed at a mass ratio of 9:1 and dissolved in N-methylpyrrolidone (NMP) to prepare a casting solution with a total solids content of 15 wt%. The solution is magnetically stirred at room temperature for 12 hours until the polyethyleneimine and aminosilane coupling agent are completely dissolved to form a homogeneous viscous solution. The solution is then allowed to stand for 2 hours to remove bubbles.
[0080] An automatic coating machine was used to coat the above casting solution onto one side of a polypropylene membrane with a wet film thickness of 100 μm. The coating speed was 1.5 m / min, the ambient temperature was 25±2℃, and the relative humidity was <30%. Immediately after coating, the polypropylene membrane coated with the casting solution was immersed in a pure water coagulation bath at 25℃ for phase inversion for 12 hours.
[0081] After phase inversion, the composite membrane was removed and rinsed repeatedly with deionized water five times to thoroughly remove residual N-methylpyrrolidone. The composite membrane was then hung to air dry at room temperature for 24 hours, followed by vacuum drying at 50°C for 6 hours, yielding a cation enrichment and protective layer 40. Field emission scanning electron microscopy (FESEM) cross-sectional observation showed that the cation enrichment and protective layer 40 was approximately 7 μm thick, possessing a finger-like macroporous structure with an average pore size of approximately 2–3 μm. XPS analysis detected an N 1s characteristic peak (binding energy approximately 399.0 eV), confirming the successful introduction of amino groups into the pore walls.
[0082] Interlayer composite: The anion repulsion layer 10 with the ion transport enhancement layer 20 and the supporting base film layer 30 with the cation enrichment and protection layer 40 are aligned and placed in the order of anion repulsion layer 10-ion transport enhancement layer 20-supporting base film layer 30-cation enrichment and protection layer 40. The stacked composite is placed in a flat plate hot press, and the hot pressing temperature is set to 55°C, the hot pressing pressure is 0.4 MPa, and the hot pressing time is 5 minutes.
[0083] After hot pressing, the pressure is kept constant, and the membrane is allowed to cool naturally to room temperature before being depressurized and removed. The composite membrane is then cut to the size required for battery assembly and vacuum dried at 60°C for 8 hours to obtain a cross-scale ion rectifying membrane with a total thickness of approximately 20 μm.
[0084] Example 2 Figure 2 This is a schematic diagram of the cross-sectional structure of a multi-scale ion rectifying membrane provided in another embodiment of this application. Figure 2 As shown, the cross-scale ion rectifier membrane of this embodiment includes, in the thickness direction from the positive electrode side to the negative electrode side, an anion repulsion layer 10, a supporting base film layer 30, and a cation enrichment and protection layer 40. The difference between this embodiment and Embodiment 1 is that the ion transport enhancement layer 20 is omitted, and the membrane structure is three layers.
[0085] An anion repulsion layer 10 is disposed on the positive electrode side and is in direct contact with the positive electrode plate of the battery during use. It is composed of a porous membrane of polyvinylidene fluoride-hexafluoropropylene copolymer grafted with sulfonic acid groups. Since the active piezoelectric driven ion transport enhancement layer 20 is omitted in this embodiment, the average pore size of the anion repulsion layer 10 is moderately enlarged to 60-70 nm to compensate for the increase in lithium-ion transport resistance without active drive. The thickness is 5 μm. The sulfonic acid groups on the pore walls also form a fixed negative charge network, generating electrostatic repulsion against anions and achieving selective lithium-ion transport.
[0086] The supporting base film layer 30 is disposed on the side of the anion repulsion layer 10 near the negative electrode side. It is the same polypropylene microporous membrane as in Example 1, with a thickness of 16 μm and an average pore size of 120 nm.
[0087] The cation enrichment and protection layer 40 is disposed on the side of the supporting base film layer 30 near the negative electrode side, and has the same structure and material as the cation enrichment and protection layer 40 in Example 1: it is made of polyethyleneimine and an aminosilane coupling agent by phase inversion, with a mass ratio of polyethyleneimine to aminosilane coupling agent of 9:1. It has a finger-like macroporous structure, the pore walls contain amino groups, the average pore size is 2 μm to 3 μm, and the thickness is 7 μm. The dual functions of the amino groups, the homogenization of lithium ion flow, and the chemical capture of hydrogen fluoride are the same as in Example 1.
[0088] The total thickness of the three-layer structure, consisting of anion repulsion layer 10, supporting base film layer 30, and cation enrichment and protection layer 40, is 18 μm.
[0089] The preparation method of the cross-scale ion rectifier membrane in this embodiment is as follows.
[0090] Preparation of anion repulsion layer 10: The same polyvinylidene fluoride-hexafluoropropylene copolymer porous membrane as in Example 1 was used as the matrix material. A grafting reaction solution with the same composition as in Example 1 was prepared (15% sodium styrene sulfonate and 5% acrylic acid). The pretreated polyvinylidene fluoride-hexafluoropropylene copolymer membrane was immersed in the grafting reaction solution at the same bath ratio as in Example 1, deoxygenated by nitrogen purging, and then sealed. The absorbed dose for cobalt-60 gamma irradiation grafting was set to 10 kGy, the dose rate to 2 kGy / h, and the irradiation temperature to room temperature.
[0091] After irradiation, the washing and drying conditions were the same as in Example 1. The grafting rate was determined to be approximately 20%–25% by weighing, and the average pore size was observed to be approximately 60–70 nm by field emission scanning electron microscopy. XPS analysis also detected the S2p characteristic peak, confirming the successful grafting of sulfonic acid groups.
[0092] Cation enrichment and preparation of protective layer 40 on supporting film layer 30: The supporting base membrane layer 30 is the same polypropylene microporous membrane as in Example 1, and the pretreatment method is the same as in Example 1. The casting solution preparation and phase inversion process of the cation enrichment and protective layer 40 are exactly the same as in Example 1: polyethyleneimine and aminosilane coupling agent are dissolved in N-methylpyrrolidone at a mass ratio of 9:1, with a total solid content of 15 wt%. The wet film thickness is 100 μm, and it is immersed in pure water at 25°C for phase inversion for 12 hours. After washing and drying, the cation enrichment and protective layer 40 is obtained.
[0093] Interlayer composite: The anion repulsion layer 10 and the supporting base film layer 30 with the cation enrichment and protection layer 40 were aligned in the order of anion repulsion layer 10-supporting base film layer 30-cation enrichment and protection layer 40, and placed in a flatbed hot press. The mixture was hot-pressed for 5 minutes at 55°C and 0.4 MPa. After natural cooling, it was cut and vacuum dried at 60°C for 8 hours to obtain a three-layer cross-scale ion rectifying membrane with a total thickness of approximately 18 μm.
[0094] Example 3 This embodiment provides a cross-scale ion rectification membrane, which differs from Embodiment 2 in that the mass ratio of polyethyleneimine to aminosilane coupling agent in the casting solution of the cation enrichment and protective layer is 8:1.
[0095] The preparation of the anion repulsion layer was exactly the same as in Example 2. The supporting base film layer was the same as in Example 1. In the preparation of the casting solution for the cation enrichment and protective layer, polyethyleneimine and aminosilane coupling agent were mixed at a mass ratio of 8:1 (based on solid content), and the remaining preparation conditions were the same as in Example 1. The conditions for coating, phase inversion, washing, and drying were all the same as in Example 1. Field emission scanning electron microscopy showed that the average pore size of the cation enrichment and protective layer was approximately 3-4 μm. Quantitative analysis using XPS showed that the atomic percentage of nitrogen on the surface of this layer was approximately 6.8%. The interlayer composite process was the same as in Example 2, resulting in a three-layer structured multi-scale ion rectifying membrane.
[0096] Example 4 This embodiment provides a cross-scale ion rectification membrane, which differs from Embodiment 2 in that the mass ratio of polyethyleneimine to aminosilane coupling agent in the casting solution of the cation enrichment and protective layer is 10:1.
[0097] The preparation of the anion repulsion layer was exactly the same as in Example 2. The supporting base film layer was the same as in Example 1. In the preparation of the casting solution for the cation enrichment and protective layer, polyethyleneimine and aminosilane coupling agent were mixed at a mass ratio of 10:1 (based on solid content), and the remaining preparation conditions were the same as in Example 1. The conditions for coating, phase inversion, washing, and drying were the same as in Example 1. Field emission scanning electron microscopy showed that the average pore size of the cation enrichment and protective layer was approximately 1.5~2.5 μm, and the atomic percentage of nitrogen on the XPS surface was approximately 8.2%. The interlayer composite process was the same as in Example 2, resulting in a three-layer structured multi-scale ion rectifying membrane.
[0098] Comparative Example 1 This comparative example provides a commercially available, best-in-class multilayer coated separator as a performance benchmark.
[0099] The membrane is a commercially available ceramic-polymer composite coated membrane. The base membrane is a 16μm polypropylene microporous membrane, coated on both sides with an alumina ceramic layer and a polyvinylidene fluoride adhesive coating, with a total thickness of approximately 20μm. This membrane represents a typical solution for electrochemically inert porous media in the current technology.
[0100] Comparative Example 2 This comparative example provides a double-layer membrane that consists only of an anion repulsion layer and a supporting base membrane layer, and does not have a cation enrichment and protection layer.
[0101] The preparation of the anion repellent layer was exactly the same as in Example 2, resulting in an anion repellent layer with an average pore size of approximately 60-70 nm. This anion repellent layer was then hot-pressed with a supporting substrate membrane (16 μm polypropylene microporous membrane) at 55 °C and 0.4 MPa for 5 minutes to obtain a bilayer membrane with a total thickness of approximately 21 μm.
[0102] Comparative Example 3 This comparative example provides a double-layer membrane that includes only a supporting base membrane layer and a cation enrichment and protection layer, but does not have an anion repulsion layer.
[0103] The preparation of the cation enrichment and protective layer on the supporting substrate membrane layer was exactly the same as in Example 2: polyethyleneimine and aminosilane coupling agent were dissolved in N-methylpyrrolidone at a mass ratio of 9:1, and coated onto the surface of a polypropylene membrane. A finger-like macroporous structure was formed through aqueous phase conversion. A bilayer membrane with a total thickness of approximately 22 μm was obtained.
[0104] Performance testing and results analysis: I. Testing Methods The separators from Examples 1-4 and Comparative Examples 1-3 were assembled into CR2032 coin-type symmetrical blocking batteries (lithium sheet | separator-electrolyte | lithium sheet). Under isothermal conditions of 25°C, the lithium-ion transference number was determined using the Bruce-Vincent steady-state current method coupled with AC impedance spectroscopy. The electrolyte was 1M LiPF6 in EC / DMC / EMC (volume ratio 1:1:1). A constant DC polarization voltage of 10 mV was applied, and the initial and steady-state currents were recorded. AC impedance spectra were measured before and after polarization.
[0105] Calculate using the following formula :
[0106] In the above formula: is the lithium-ion transference number (dimensionless, 0~1). This is the initial current (the steady-state current before polarization, which is usually very small, close to 0). This refers to the steady-state current (the current that reaches a stable state after a period of time following the application of a constant polarization voltage). The applied constant polarization voltage (typically 10 mV or 20 mV); The initial interface resistance (the total battery resistance measured by AC impedance before polarization).
[0107] The steady-state interface resistance (the total battery resistance measured again after polarization reaches a steady state).
[0108] Each sample was tested with three parallel cells, and the arithmetic mean was taken.
[0109] The separators from each embodiment and comparative example were assembled into 2.0 Ah pouch cells, with NCM811 (LiNi0.8Co0.1Mn0.1O2) as the positive electrode and artificial graphite as the negative electrode. Charge-discharge cycle tests were conducted at a constant temperature of 25°C and a current density of 1C / 1C, and the charge-discharge energy efficiency (η = discharge energy / charge energy × 100%) was recorded after the 1000th cycle. Five cells were tested for each sample, and the average value was taken. At 50% charge, a 3C current pulse discharge for 10 seconds was applied, and the DC internal resistance was calculated.
[0110] II. Test Results The performance test results of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.
[0111] Table 1:
[0112] III. Results Analysis As shown in Table 1, the lithium-ion transference number of Example 1 reached 0.62, an improvement of approximately 77% compared to Comparative Example 1 (0.35). The energy efficiency reached 96.8%, an improvement of 0.4 percentage points compared to Comparative Example 1 (96.4%). The 3C DC internal resistance was 38.5 mΩ, a decrease of 18.1% compared to Comparative Example 1 (47.0 mΩ). This indicates that the fixed negatively charged groups in the anion repulsion layer effectively suppressed the reactive migration of anions through electrostatic repulsion. At the same time, the piezoelectric material in the ion transport enhancement layer converted electrode deformation into additional driving force to actively compensate for concentration polarization. The synergy of these two factors achieved a leapfrog progress in membrane technology.
[0113] Example 2 achieved an energy efficiency of 96.6%, an improvement of 0.2 percentage points compared to Comparative Example 1, and a 3C DC internal resistance of 42.1 mΩ, a decrease of 10.4% compared to Comparative Example 1. This demonstrates that even without active piezoelectric drive, the electrostatic sieving effect of the anion repulsion layer alone can achieve an energy efficiency level exceeding that of the prior art, and the cation enrichment and amino coordination homogenization effect of the protective layer further ensures interface stability.
[0114] The energy efficiency of Example 3 was 96.4%, the same as Comparative Example 1. When the ratio of polyethyleneimine to aminosilane coupling agent decreased to 8:1, the atomic percentage of nitrogen on the surface of the cation enrichment and protective layer decreased to approximately 6.8%. The decrease in amino density led to homogenization of lithium-ion flow and weakened HF capture effect, partially offsetting the gain provided by the anion repulsion layer. The energy efficiency of Example 4 was 96.6%, comparable to Example 2, with an atomic percentage of nitrogen on the XPS surface of approximately 8.2%, demonstrating that the 10:1 ratio of cation enrichment and protective layer can provide sufficient functional group density.
[0115] Comparative Example 2 (anion repulsion layer + supporting base film layer only) had an energy efficiency of 96.3%, only 0.1 percentage points higher than Comparative Example 1. Although its lithium-ion transference number (0.50) was significantly better than Comparative Example 1, due to the lack of a finger-like macroporous structure for cation enrichment and protection, lithium ions selected by the anion repulsion layer locally accumulated at the micropore interface of the supporting base film layer, causing increased concentration polarization at the interface and partially offsetting the gain of the anion repulsion layer. This conversely verifies the necessity of the "finger-like macroporous through-release" structural design of the cation enrichment and protection layer. The anion repulsion layer is responsible for sieving, while the cation enrichment and protection layer is responsible for smooth release and interface homogenization; both are indispensable.
[0116] Comparative Example 3 (supporting base film layer + cation enrichment and protective layer only) had a lithium-ion transference number of only 0.33 and an energy efficiency of 95.8%, which was lower than that of Comparative Example 1. This indicates that the membrane containing only the cation enrichment and protective layer but without the anion repulsion layer cannot suppress the reactive migration of anions, and the increased thickness of the cation enrichment and protective layer actually increases the ion transport resistance, leading to a decrease in overall performance.
[0117] The cross-scale ion rectifying separator and its preparation method provided in this application, along with lithium-ion batteries, have the following advantages: (1) By constructing a three-layer asymmetric structure of anion repulsion layer-support base film layer-cation enrichment and protection layer in the thickness direction of the membrane, the fixed negative charge groups of the anion repulsion layer increase the transmembrane transport resistance of lithium salt anions by more than two orders of magnitude through electrostatic repulsion effect, and the lithium ion transference number increases from 0.35 to more than 0.50, thereby reducing the concentration polarization loss caused by reactive migration of anions from the root.
[0118] (2) An ion transport enhancement layer is further provided between the anion repulsion layer and the supporting base film layer. The piezoelectric material in this layer generates an instantaneous piezoelectric potential difference by utilizing the volume deformation of the electrode, which acts as an "ion pump" to actively drive the lithium ion cross-film transport, effectively compensating for the interface concentration polarization during high-rate charging and discharging. The 3C DC internal resistance is reduced by more than 18% compared with the best commercial separator.
[0119] (3) The cation enrichment and protection layer has a finger-like macroporous structure with amino groups on the pore walls. It has the dual functions of lithium ion flow homogenization and hydrogen fluoride chemical capture, which not only inhibits the growth of lithium dendrites, but also protects the negative electrode SEI film, significantly extending the cycle life of the battery.
[0120] (4) Each functional layer is prepared independently and then composited. The process conditions do not interfere with each other, and all of them adopt mature industrial technologies (irradiation grafting, phase conversion, hot pressing composite). They are compatible with existing lithium battery separator production lines and can achieve large-scale production without major equipment modifications.
[0121] Therefore, the cross-scale ion rectifier separator and its preparation method provided in this application have extremely high industrial practical value and broad market application prospects for lithium-ion batteries.
[0122] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A multi-scale ion rectifier membrane, characterized in that, The membrane, in the thickness direction from the positive electrode side to the negative electrode side, comprises, in sequence: an anion repulsion layer, a supporting base membrane layer, and a cation enrichment and protection layer; The anion repulsion layer is a porous membrane with an average pore size of 20nm~80nm, and the pore walls are equipped with fixed negatively charged groups. The supporting substrate membrane layer is a microporous membrane; The cation enrichment and protective layer is a porous membrane with an average pore size of 1 μm to 5 μm, and the pore walls contain electron-donating groups.
2. The cross-scale ion rectifier membrane according to claim 1, characterized in that, The membrane further includes: an ion transport enhancement layer disposed between the anion repulsion layer and the supporting base film layer; The ion transport enhancement layer comprises a piezoelectric material.
3. The cross-scale ion rectification membrane according to claim 2, characterized in that, The ion transport enhancement layer comprises a composite material of piezoelectric material and ion-conducting polymer; The piezoelectric material is at least one piezoelectric ceramic nanoparticle selected from tetragonal barium titanate, lead zirconate titanate and potassium sodium niobate, or a β-crystal piezoelectric polymer of polyvinylidene fluoride-trifluoroethylene copolymer. The ion-conducting polymer comprises polyethylene oxide and lithium bis(trifluoromethanesulfonylimide).
4. The cross-scale ion rectification membrane according to claim 2, characterized in that, The thickness of the ion transport enhancement layer is 1μm to 3μm, and the average pore size is 50nm to 200nm.
5. The cross-scale ion rectifying membrane according to claim 1, characterized in that, The thickness of the anion repulsion layer is 2 μm to 5 μm; The supporting base membrane layer is a polypropylene microporous membrane or a polyethylene microporous membrane with a thickness of 5 μm to 25 μm. The thickness of the cation enrichment and protective layer is 5 μm to 10 μm.
6. The cross-scale ion rectifying membrane according to claim 1, characterized in that, The anion repellent layer is composed of a matrix material grafted with and fixed negatively charged groups; Wherein, the fixed negative charge group is a sulfonic acid group or a carboxyl group; The matrix material includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polypropylene, polyethylene, sulfonated polyether ether ketone, and perfluorosulfonic acid resin.
7. The cross-scale ion rectifier membrane according to claim 1, characterized in that, The cation enrichment and protective layer is made of polyethyleneimine and aminosilane coupling agent by phase inversion method; The electron-donating group is an amino group.
8. The cross-scale ion rectifying membrane according to claim 7, characterized in that, The mass ratio of the polyethyleneimine to the aminosilane coupling agent is 8:1 to 10:
1.
9. A method for preparing a cross-scale ion rectifier membrane, characterized in that, Including the following steps: An anion repulsion layer is formed, wherein the anion repulsion layer has an average pore size of 20nm~80nm and the pore walls are equipped with fixed negatively charged groups. A supporting base film layer is formed, wherein the supporting base film layer is a microporous membrane; A cation enrichment and protective layer is formed, wherein the cation enrichment and protective layer is a porous membrane with an average pore size of 1 μm to 5 μm and the pore walls contain electron-donating groups; The anion repulsion layer, the supporting base film layer, and the cation enrichment and protection layer are aligned sequentially from the positive electrode side to the negative electrode side in the thickness direction, and then hot-pressed together to form a cross-scale ion rectification membrane.
10. The preparation method according to claim 9, characterized in that, The formation of the anion repulsion layer includes the following steps: The polymer porous membrane was immersed in a mixed aqueous solution containing styrene sulfonate monomer and acrylic acid, and grafted by co-irradiation with cobalt-60 γ-rays under an inert atmosphere with an absorbed dose of 10 kGy ~ 15 kGy. After grafting, the membrane was washed and dried to obtain an anion repulsion layer grafted with sulfonic acid groups. The formation of the cation enrichment and protective layer includes the following steps: dissolving polyethyleneimine and aminosilane coupling agent in N-methylpyrrolidone at a mass ratio of (8~10):1 to form a casting solution; scraping the casting solution onto the side of the supporting substrate film layer near the negative electrode; and then immersing it in water for phase inversion to obtain the cation enrichment and protective layer.
11. The preparation method according to claim 9, characterized in that, Also includes: An ion transport enhancement layer is formed between the anion repulsion layer and the supporting substrate film layer, the ion transport enhancement layer comprising a piezoelectric material.
12. The preparation method according to claim 9, characterized in that, The formation of the ion transport enhancement layer includes the following steps: A piezoelectric material and an ion-conducting polymer are mixed and dispersed in an organic solvent to form a slurry. The slurry is then coated onto the surface of the anion repulsion layer and dried under vacuum to obtain the ion transport enhancement layer.
13. The preparation method according to claim 12, characterized in that, The piezoelectric material is tetragonal barium titanate nanoparticles, and the ion-conducting polymer comprises polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide; the mass ratio of the tetragonal barium titanate nanoparticles, the polyethylene oxide and the lithium bis(trifluoromethanesulfonyl)imide is (65~75):(20~30):(3~8).
14. The preparation method according to claim 9, characterized in that, The hot-pressing composite temperature is 50~60℃, and the pressure is 0.3MPa~0.5MPa.
15. The preparation method according to claim 9, characterized in that, The thickness of the anion repulsion layer is 2 μm to 5 μm; the thickness of the supporting base film layer is 5 μm to 25 μm; and the thickness of the cation enrichment and protection layer is 5 μm to 10 μm.
16. A lithium-ion battery, characterized in that, It includes the cross-scale ion rectifier membrane as described in any one of claims 1 to 8, or the cross-scale ion rectifier membrane prepared by the preparation method as described in any one of claims 9 to 15.